The Effect of Bar Diameter on Bond Stress of Geopolymer Concrete with Pull-out Test - Ashara, Khansa Fadilah; Piscesa, Bambang; Tajunnisa, Yuyun (Journal of Civil Engineering, 2024)
Geopolymer concrete, an eco-friendly alternative, employs silica, alumina, and alkaline activators. While wet mixing has been extensively studied, its limitations, such as impracticality, quick setting, and low workability, are overcome by the dry mixing method. Study by previous research is limited only to compressive strength, flexural strength, and shrinkage. However, research on bond strength, crucial for concrete-reinforcement adhesion, is limited. This study investigates bond strength through pull-out tests using consistent concrete materials, including Type C fly ash, 12M NaOH, and an alkali ratio of 1:1. Specimens with varying reinforcement diameters (D10, D12, D16) and additional transverse reinforcement (f6-150) were tested. Bond stress averages at D10, D12, and D16 are 25.80 MPa, 25.36 MPa, and 24.25 MPa. Reinforcement diameter directly influences bond strength, with larger diameters yielding greater bond stress.